Strengthening Community University Research Partnerships Global Perspectives - Tremblay, Crystal; Tandon, Rajesh; Hall, Budd (University of Victoria Libraries, 2015)
This volume is the most comprehensive and up-to-date international analysis of community research partnerships available to date. It presents the first-ever global survey on the topic and 12 country case studies written by leading academics and practitioners from around the world. Communicating insights from both the Global South and North, the authors describe and explain global trends, challenges and effective approaches. A source of both inspiration and practical guidance, it is must reading for national policy-makers, university officials and professors, and civil society practitioners.